Inside Cover: Selenylation Chemistry Suitable for On‐Plate Parallel and On‐DNA Library Synthesis Enabling High‐Throughput Medicinal Chemistry (Angew. Chem. Int. Ed. 35/2022). Issue 35 (4th July 2022) - Xu, Hongtao; Wang, Yan; Dong, Hewei; Zhang, Yiyuan; Gu, Yuang; Zhang, Shuning; Meng, Yu; Li, Jie; Shi, Xiao Jie; Ji, Qun; Liu, Lili; Ma, Peixiang; et al.
Abstract : Selenium is an emerging versatile player in medicinal chemistry. In their Research Article (e202206516 ), Hongtao Xu, Fei Ma, Guang Yang, Wei Hou et al. introduce a bioinspired SeClick chemistry between indole and benzoselenazole, which can be used in on‐plate parallel synthesis of indole‐selenide libraries and selenium containing DNA‐encoded libraries ( Se DELs) in a modular and predictable way, thereby boosting the development of seleno‐medicinal chemistry in the near future.